Pengaplikasian Mikroba dalam Sediaan Fermentasi Makanan dan Minuman bagi Kesehatan Manusia - Supartiningsih Supartiningsih; Syahira Syahira; Kemuning Zalianti; Wahyuni Sabina; Sofi Suci Sibagariang; Elisa Septiani Silalahi; Riska Wahyu Ningsih; Rival Kasnurlin Gulo; Tri She Wira U.B Sitompul; Saskia Dintapryana; Deya Rahmahyanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Fermented foods and beverages containing probiotic microorganisms provide substantial health benefits, yet public understanding of how these microbes work remains limited in many parts of Indonesia. This review examines fifteen published community-education and outreach articles on the application of fermentation microbes in food and beverages, focusing on the microbiological and probiotic mechanisms underlying these programs and their impact on public knowledge. A descriptive literature review was conducted on fifteen nationally published Indonesian journal articles (2019-2025), extracting the fermentation substrate, probiotic microorganisms involved, education method, and outcome of each activity, followed by comparative-descriptive analysis. All reviewed activities reported measurable knowledge improvement, with post-test scores consistently higher than pre-test scores, some reaching full comprehension among participants. The most frequently applied probiotics were Lactobacillus and Bifidobacterium, together with the SCOBY consortium used in kombucha, kefir, and yogurt, as well as products derived from local ingredients such as salak, pineapple peel, orange sweet potato, and Podang mango. Mechanistically, these probiotics act through competitive exclusion of pathogens, production of antimicrobial metabolites such as bacteriocins, and modulation of the immune system via gut-associated lymphoid tissue, thereby maintaining gut microbiota balance and preventing dysbiosis. Community education that combines an understanding of microbial fermentation mechanisms with hands-on training using local ingredients effectively improves public knowledge, skills, and health awareness regarding probiotic fermented foods, and represents a promising strategy for future public-health outreach in Indonesia.